New Results in Numerical and Experimental Fluid Mechanics XI Contributions to the 20th STAB/DGLR Symposium Braunschweig, Germany, 2016 - Dillmann, Andreas; Heller, Gerd.; Krämer, Ewald; Wagner, Claus; Bansmer, Stephan; Radespiel, Rolf.; Semaan, Richard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers contributions to the 20th biannual symposium of the German Aerospace Aerodynamics Association (STAB) and the German Society for Aeronautics and Astronautics (DGLR). The individual chapters reflect ongoing research conducted by the STAB members in the field of numerical and experimental fluid mechanics and aerodynamics, mainly for (but not limited to) aerospace applications, and cover both nationally and EC-funded projects. Special emphasis is given to collaborative research projects conducted by German scientists and engineers from universities, research-establishments and industries. By addressing a number of cutting-edge applications, together with the relevant physical and mathematics fundamentals, the book provides readers with a comprehensive overview of the current research work in the field. Though the book's primary emphasis is on the aerospace context, it also addresses further important applications, e.g. in ground transportation and energy.
PART I: New Results in Numerical and Experimental Fluid Mechanics XI -- PART II: Turbulence Research and Turbulence Modeling -- PART III: Hypersonic Aerodynamics -- PART IV: Laminar Flow Control and Transition -- PART V: High-Agility Configuration -- PART VI: Rotorcraft Aerodynamics -- PART VII: Aeroelasticity and Structural Dynamics -- PART VIII: Numerical Simulation/Aerodynamics -- PART IX: Experimental Aerodynamics/Experimental Simulation and Test Techniques -- PART X: Aeroacoustics -- PART XI: Vehicle Aerodynamics -- PART XII: Wind Energy.
Keywords: Fluid mechanics; Continuum mechanics; Aerospace engineering; Astronautics; Engineering Fluid Dynamics; Continuum Mechanics; Aerospace Technology and Astronautics